Bariatric surgery‐induced weight loss in patients with and without type 2 diabetes mellitus. Issue 2 (21st January 2020) - Carvalho, Thatiany A.; Ronsoni, Marcelo F.; Hohl, Alexandre; van de Sande‐Lee, Simone
Summary: Surgical treatment of obesity leads to weight loss and metabolic improvement, but it is unclear if the response differs between patients with and without type 2 diabetes. Retrospective cohort study comparing weight loss and metabolic outcomes between patients with and without type 2 diabetes, matched for body mass index (BMI), gender and age, 12 months after Roux‐en‐Y gastric bypass. Forty‐eight patients with type 2 diabetes (D) and 48 without type 2 diabetes (ND) were evaluated, 87.5% female, mean age 42.2 ± 0.9 years. The mean baseline weight and BMI of the D and ND groups were, respectively, 120.3 ± 21.6 vs 123.7 ± 20.8 kg ( P = .45) and 47.2 ± 7.5 vs 47.2 ± 6.9 kg/m 2 ( P = .70). After 12 months, there was no significant difference in weight (40.4 ± 16.9 vs 44.1 ± 12.2 kg, P = .28) and BMI (15.8 ± 6.5 vs 16.9 ± 4.5 kg/m 2, P = .26) variation between groups. The parameters that presented significant variation were (D vs ND): fasting blood glucose (41.6 ± 43.0 vs 12.7 ± 17.2 mg/dL, P  < .01), HbA1c (1.8 ± 1.6 vs 0.6 ± 0.7%; P  < .01), triglycerides (91.1 ± 100.4 vs 54.2 ± 43.8 mg/dL; P = .04), low‐density lipoprotein (27.2 ± 41.5 vs 37.5 ± 24.2 mg/dL; P  < .01) and gamma glutamyl transferase (46.5 ± 55.3 vs 17.7 ± 11.9 UI/L; P = .04). Weight loss 12 months after a gastric bypass was similar in patients with and without type 2 diabetes, the greater metabolic benefits appearing in patients with type 2 diabetes as they had more pronounced changes at baseline.